Exploring the impact of cyber and traditional crime victimization: Impact comparisons and explanatory factors - Borwell, Jildau (International review of victimology, 2025)
As cybercrime victimization rates continue to rise, our understanding of their impact, especially compared to traditional crime, remains limited. To address this knowledge gap, we conducted surveys among 910 crime victims, measuring the impact of cyber and traditional variants of property, person-centered, and sexual crime. We compared the impact of: (1) residential burglary and hacking of online bank accounts; (2) doorstep deception and bank helpdesk fraud; (3) in-person threats and online threats; and (4) sexual assault and image-based sexual abuse. Impact was categorized into peritraumatic stress, internalizing problems, externalizing problems, financial impact, and damaged self-image. Our findings reveal that cybercrime impact mostly equals or exceeds that of traditional crimes. Disparities especially emerge in terms of higher peritraumatic stress experienced by victims of cyber property crime, and more damage to self-image suffered by victims of both cyber property and cyber sexual crimes. Furthermore, we identified significant determinants of victim impact among crime characteristics, and social, personal, and demographic factors, some varying between cyber and traditional crime. Our study emphasizes the implications of the technological nature of cybercrime and the relatively active role played by cybercrime victims, while also considering the issue of victim blaming. Furthermore, we underscore the need for targeted victim support and prioritization of cybercrime.